Grade Assignment by Ki-67 Proliferative Index, Mitotic Count, and Phosphohistone H3 Count in Surgically Resected Gastrointestinal and Pancreatic Neuroendocrine Tumors. Issue 10 (November 2017) - Murphy, Claire E.; McCormick, Kinsey A.; Shankaran, Veena; Reddi, Deepti M.; Swanson, Paul E.; Upton, Melissa P.; Papanicolau-Sengos, Antonios; Khor, Sara; Westerhoff, Maria
Abstract : Objectives: The aim of this study was to evaluate the concordance in grade assignment for gastroenteropancreatic neuroendocrine tumors using mitotic count (MC), Ki-67 proliferative index (KPI), and phosphohistone H3 count (PHH3C). Methods: Resected gastroenteropancreatic neuroendocrine tumors were graded based on MC, KPI, and PHH3C. Concordance was determined using a weighted κ statistic. Median survival across each grade category was determined using Kaplan-Meier methods. Results: Of the 110 patients, the majority had gastrointestinal primaries and grade 1 or 2 tumors. Rates of discordance in grade assignment were 29% of cases for KPI versus MC (κW = 0.26), 32% for PHH3C versus MC (κW = 0.34), and 32% for PHH3C versus KPI (κW = 0.37). There was fair agreement between grading by KPI and MC. Relative to grade by KPI and MC, PHH3C tended to upgrade tumors. The proportion alive at 3 and 5 years was not significantly different for patients with grade 1 versus grade 2 tumors. Conclusions: The concordance between KPI and MC was fair. Phosphohistone H3 count tended to upgrade tumors using the cutoffs established by MC. Grade 1 and grade 2 tumors were associated with similar survival regardless of grading method. The overall relevance of the current cutoff values used in grading neuroendocrine tumors may need to be revisited.